2022
DOI: 10.1007/s40618-022-01957-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone mirrors inflammation parameters in females hospitalized with COVID-19

Abstract: Background While low testosterone (T) was described as a predictor of unfavorable coronavirus-disease 19 outcome in men, data concerning the role of T in women with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are scant and limited to small cohorts. This study investigated the relationship between serum T values and outcomes of COVID-19 in a large female hospitalized cohort. Methods One-hundred-sixty-eight adult women (median age 77, range 18-100 years; 154 in post-menopause) hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Earlier research has shown that decreased testosterone levels were associated with increased CRP, PCT, and interleukin (IL)-6 levels in patients with COVID-19 ( 25 , 26 ). Furthermore, lower testosterone levels correlated with higher APACHE II and SOFA scores and independently predicted higher mortality in patients with SIC ( 27 ). Thus, declining testosterone levels could indicate worsening sepsis severity and increased mortality risk in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that decreased testosterone levels were associated with increased CRP, PCT, and interleukin (IL)-6 levels in patients with COVID-19 ( 25 , 26 ). Furthermore, lower testosterone levels correlated with higher APACHE II and SOFA scores and independently predicted higher mortality in patients with SIC ( 27 ). Thus, declining testosterone levels could indicate worsening sepsis severity and increased mortality risk in male patients.…”
Section: Discussionmentioning
confidence: 99%